Current research in DNA repair - Douglas, Albert (United States : States Academic Press, 2021)
DNA repair refers to all the processes through which a cell identifies the damage to the DNA molecules and corrects them. Environmental factors such as radiations and normal metabolic activities can cause damage to the DNA which results in number of individual lesions per cell per day. These lesions can cause structural damage to the DNA molecule which in turn can lead to alteration in the cell's ability to transcribe the gene that is encoded by the affected DNA. On the basis of the type of damage in the DNA's double helical structure, there are various types of DNA repair mechanisms such as direct reversal, base excision repair, nucleotide excision repair, and mismatch repair systems, etc. The book aims to shed light on some of the unexplored aspects of DNA repair and the recent researches in this field. It studies, analyses and upholds the pillars of DNA repair and its utmost significance in modern times. This book is a complete source of knowledge on the present status of this important field.
Includes index.
Includes bibliographical references.
Keywords: DNA repair; DNA damage; Biochemical genetics; Antimutagens